The use of Gamma Distribution to Evaluate Water Pollutants in Asejire Reservior, Ibadan (Fountain Journal of Natural and Applied Sciences, 2013)
This research work under-studies the application of probability functions to water pollution data with some related works. It figures out two parameter gamma distribution fitted to monitor the concentration of five water pollutants in Asejire reservoir; Turbidity, Colour, pH, Dissolved Oxygen and Alkalinity, by estimating the parameters and testing the goodness of fit. It was discovered that all the considered pollutants could be modeled with gamma distribution as confirmed by the Kolmogorov Smirnov (KS) test. It was also found that all the pollutants were significant except Dissolved Oxygen. The technique and results presented in this study provide a foundation for the use of gamma distribution to model water pollutants. The model is used as decision support tools for the management of the reservoir, as the attention of government and stake-holders must be drawn to keeping water safe for sustainable development.Keywords: Pollution, Kolmogorov Smirnov test, Gamma Distribution, Estimation, Shapiro-Wilk